An Emerging Zoonosis of Public Health Concern: A Comprehensive Review on Nipah Virus Infection - Chimire, Kripa; Kasarla, Rajeshwar Reddy; Adhikari, Shristi Raut; Pathak, Laxmi (Journal of Universal College of Medical Sciences, 2022)
Nipah virus (NiV) infection is an emerging zoonotic disease, which causes encephalitis and respiratory infections in humans with high mortality rate. Bats (Pteropus) are the natural hosts for for Nipah virus. The infection is transmitted from bats (Pteropus) to pigs and from pigs to humans or human-to-human. Clinical symptoms include fever, headache, dizziness, vomiting followed by drowsiness, disorientation, mental confusion, and neurological signs that indicate acute encephalitis. Due to lack of vaccines and effective antiviral drugs, and diagnostics, NiV infection poses a serious public health concern. The knowledge and scientific information on Nipah virus infection is still unknown or relatively limited to many clinicians, and received little attention; hence this comprehensive review of Nipah virus infection is undertaken to highlight its importance and further research.